2022
DOI: 10.2215/cjn.10300721
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination and COVID-19 Dynamics in Dialysis Patients

Abstract: Background and objectivesDialysis patients have a high mortality risk after coronavirus disease 2019 (COVID-19) and an altered immunologic response to vaccines, but vaccine clinical effectiveness remains unknown in this population.Design, setting, participants, & measurementsUsing Bayesian multivariable spatiotemporal models, we estimated the association between vaccine exposure and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) severe infections (with hospital admission) in dialysis patients… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 23 publications
5
29
0
Order By: Relevance
“…Patients with chronic kidney disease (CKD), especially those with end-stage kidney disease (ESKD) undergoing maintenance hemodialysis (HD), are at high risk of COVID-19 severity and death [ 7 , 8 ]. Although patients undergoing HD are often excluded from vaccine trials for safety reasons, the results of many cohort studies have shown that SARS-CoV-2 mRNA vaccination reduces the risk of COVID-19 infection, severe illness, and death in patients receiving dialysis [ 9 , 10 ]. Therefore, SARS-CoV-2 mRNA vaccination is now recommended for patients undergoing HD.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with chronic kidney disease (CKD), especially those with end-stage kidney disease (ESKD) undergoing maintenance hemodialysis (HD), are at high risk of COVID-19 severity and death [ 7 , 8 ]. Although patients undergoing HD are often excluded from vaccine trials for safety reasons, the results of many cohort studies have shown that SARS-CoV-2 mRNA vaccination reduces the risk of COVID-19 infection, severe illness, and death in patients receiving dialysis [ 9 , 10 ]. Therefore, SARS-CoV-2 mRNA vaccination is now recommended for patients undergoing HD.…”
Section: Introductionmentioning
confidence: 99%
“…Vaccines 2022, 10, 1064 2 of 14 rate in this population [3,4]. In comparison with other vaccine platforms, the inactivated SARS-CoV-2 vaccine appears to induce weaker humoral immunity (HMI) in immunocompromised persons [5], including those on dialysis [6][7][8].…”
Section: Incidence and Hospitalizationmentioning
confidence: 99%
“…Dialysis patients are at increased risk of infection and mortality from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), owing to immunological dysfunction and comorbidities [ 1 , 2 ]. Despite the impaired vaccine response in dialysis patients, COVID-19 immunization reduces the COVID-19 incidence and hospitalization rate in this population [ 3 , 4 ]. In comparison with other vaccine platforms, the inactivated SARS-CoV-2 vaccine appears to induce weaker humoral immunity (HMI) in immunocompromised persons [ 5 ], including those on dialysis [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In hemodialysis patients, a SARS-CoV-2 infection is associated with a markedly increased morbidity and mortality in comparison to the general population with a mortality rate of more than 20% in hospitalized patients [1][2][3] . In the last two years we have learned that double vaccination might not be enough to achieve adequate long-term immune protection in all hemodialysis patients and triple vaccination offers significantly better protection against COVID-19 in this patient group 1,4 . Even if an infection cannot always be prevented after booster vaccination, the course of the COVID-19 disease in general is milder depending on the number of vaccinations in hemodialysis patients 5 .…”
Section: Introductionmentioning
confidence: 99%